MAIN PROBLEMS OF USING THE FULL POST-EDITING MODEL BASED ON MACHINE LEARNING FOR ENGLISH-KAZAKH TRANSLATION - Rakhimova Диана; Жақыпбаева, Камила (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Machine learning is one of the main branches of artificial intelligence. Its main idea is not only to use an algorithm written by a computer, but also to learn how to solve a problem on your own. Recently, in the field of translation, the issue of using machine learning and its integration with translator fixes has become very relevant. This new direction in professional English translation is called post-edited machine translation (PEMT) or post-edited machine translation (MTPE). Since the collaborative work of man and machine has given good results, this, in turn, sparked interest in post-editing and the development of automated post-editing systems. The article analyzes the advantages, disadvantages of the currently widely used online translation systems from English into Kazakh. The implementation of machine learning requires a large number of corpuses in English and Kazakh. The article contains code, results that allow you to collect corpuses.